Self-assembly of photosensitive and radiotherapeutic peptide for combined photodynamic-radio cancer therapy with intracellular delivery of miRNA-139-5p. (15th August 2021) - Wang, Hanhua; Wang, Ziyi; Chen, Weiwei; Wang, Wencai; Shi, Woda; Chen, Jinzhong; Hang, Ye; Song, Jin; Xiao, Xiao; Dai, Zhenyu
Graphical abstract: Abstract: Background: A significant challenge in cancer therapy is to maximize the therapeutic efficacy and minimize the side effects. In the past decade, a lot of nanoparticles have been used as the carriers for efficient drug delivery. Methods and Results: This study was to prepare R9 modified with 125 I-labeled cRGD and ce6 which self-assembled with miR-139-5p to form nanoparticles (Ce6-R9- 125 I-RGD-MNPs), and to further take advantage of the enhanced permeability and retention (EPR) effect of radiolabeled nanoparticles to realize the integration of tumor diagnosis and treatment. We successfully synthesized and represented it, saline and serum stability experiments demonstrating good stability. Moreover, Ce6-R9- 125 I-RGD-MNPs showed superior tumor targeting and the effect of combined photodynamic therapy (PDT) and radiotherapy treatment in vivo and vitro. Conclusion: The pathological results further confirmed that the therapeutic doses of Ce6-R9- 125 I-RGD-MNPs cause pathological changes of tumor tissues while showing minimal toxicity to normal tissues.